The Development of Bilbo Baggins Character through Leadership in J.R.R. Tolkiens The Hobbit - Iline Megale; F.X. Dono Sunardi (Journal of Language and Literature, 2017)
Leadership has been interesting since it refers to a significant quality applicable to a wide context of humans life. Traditionally, there are two points of views related to leadership. One sees it is a trait one was being born with, and the other as a cultivated trait. Galton (1869) suggests how extraordinary intelligence as an important key of leadership is something inherited. However, this view has been challenged by newer theories, being one of them is servant-leadership introduced by Greenleaf in 1977. This model believes that in order to become a leader, one must firstly learn how to be a servant. The Hobbit (1937) by J.R.R. Tolkiens is a great showcase as to how servant-leadership is cultivated along the personal development of its main character, Bilbo Baggins. The novel narrates how Bilbo joins an expedition of dwarves as a servant and through these he learns how to become a leader. Since the focus is the character development of Bilbo and the servant-leadership attributes he cultivates along the way, this research employs qualitative method. The finding confirms the presumption that Bilbo Baggins is a round and dynamic character because of its complexities and developments throughout the story. Toward the end of the story, Bilbo succeeds in developing nine leadership attributes, i.e. vision, honesty, integrity, trust, service, modeling, pioneering, appreciation of others, and empowering. These attributes are not something Bilbo naturally endowed with, but he develops, practices, and cultivates them. It is also found that the attribute of service, as the heart of servant-leadership, is dominant in Bilbo Baggins. The findings also suggest that leadership as a trait is something that can be learned from an exploration into a literary work.Key words: leadership, servant-leadership, character development